Gravity Wave Investigations over Comandante Ferraz Antarctic Station in 2017: General Characteristics, Wind Filtering and Case Study - Gabriel Augusto Giongo; José Valentin Bageston; Cosme Alexandre Oliveira Barros Figueiredo; Cristiano Max Wrasse; Hosik Kam; Yong Ha Kim; Nelson Jorge Schuch (Atmosphere, 2020)
This work presents the characteristics of gravity waves observed over Comandante Ferraz Antarctic Station (EACF: 62.1° S, 58.4° W). A total of 122 gravity waves were observed in 34 nights from March to October 2017, and their parameters were obtained by using the Fourier Transform spectral analysis. The majority of the observed waves presented horizontal wavelength ranging from 15 to 35 km, period from 5 to 20 min, and horizontal phase speed from 10 to 70 ± 2 m·s−1. The propagation direction showed an anisotropic condition, with the slower wave propagating mainly to the west, northwest and southeast directions, while the faster waves propagate to the east, southeast and south. Blocking diagrams for the period of April–July showed a good agreement between the wave propagation direction and the blocking positions, which are eastward oriented while the waves propagate mainly westward. A case study to investigate wave sources was conducted for the night of 20–21 July, wherein eight small-scale and one medium-scale gravity waves were identified. Reverse ray tracing model was used to investigate the gravity wave source, and the results showed that six among eight small-scale gravity waves were generated in the mesosphere. On the other hand, only two small-scale waves and the medium-scale gravity wave had likely tropospheric or stratospheric origin, however, they could not be associated with any reliable source.